Criminalising social policy : anti-social behaviour and welfare in a de-civilised society - Rodger, John J. (Willan, 2008)
Recent legislative and policy developments in contemporary Britain have ushered in a new approach to criminal justice. The focus on criminal dispositions and welfarism has given way to a strategy which now involves the management of social exclusion, dysfunctional and anti-social families and situational crime prevention, leading to what has been widely characterized as the 'criminalisation of social policy' - and evidenced most recently by the anti-social behaviour and respect agendas. This book is concerned to explore, analyse and explain these developments. It seeks at the same time to situ.